2017
DOI: 10.1016/j.matchemphys.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tin pest for cleaning tin-drop contaminated optics

Abstract: Highlights Tin pest induction leads to embrittlement of tin drops after β → α Sn transformation.  The purity grade influences the transformation speed of tin very strongly.  Tin drops on multilayer-coated optics disintegrate after β → α Sn transformation.  Tin drop contamination of optics is cleaned via phase transformation at -24 °C.  Reflectance of multilayer-coated mirrors is restored after tin drop transformation. Graphical Abstract AbstractTin pest, the allotropic β → α phase transformation of tin, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…After the samples were taken out of the chamber, inspection showed that the contamination was indeed fully removed without any residues. It was shown previously 20 that such fast transformation rates to α-Sn can be achieved provided the material purity grade of tin is 99.999%. The required purity for operation of the tin droplet generator in the commercial source is also at a level of at least 99,999%.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…After the samples were taken out of the chamber, inspection showed that the contamination was indeed fully removed without any residues. It was shown previously 20 that such fast transformation rates to α-Sn can be achieved provided the material purity grade of tin is 99.999%. The required purity for operation of the tin droplet generator in the commercial source is also at a level of at least 99,999%.…”
Section: Discussionmentioning
confidence: 94%
“…Gray tin seed powder was prepared by temperature cycling of tin pieces with repeated transformation between the α-Sn and β-Sn phase, as was described previously. 17 In most cases, but not always, inoculation of tin drops with α-Sn seeds was done within a few hours after tin dripping.…”
Section: Experimental Setup Vacuum Equipment and Methodologymentioning
confidence: 99%
See 3 more Smart Citations